Computational comparative analysis identifies potential stemness-related markers for mesenchymal stromal/stem cells - Ghabriel, Myret; El Hosseiny, Ahmed; Moustafa, Ahmed; Amleh, Asma (Frontiers in Cell and Developmental Biology, 2023)
Mesenchymal stromal/stem cells (MSCs) are multipotent cells that reside in multiple tissues are capable of self-renewal and differentiation into various cell types. These properties make them promising candidates for regenerative therapies. MSC identification is critical in yielding pure populations for successful therapeutic applications; however, the criteria for MSC identification proposed by the International Society for Cellular Therapy (ISCT) are inconsistent across different tissue sources. This study aimed to identify potential markers to be used together with the ISCT criteria to provide a more accurate means of MSC identification. Thus, we carried out a computational comparative analysis of the gene expression in human and mouse MSCs derived from multiple tissues to identify the differentially expressed genes that are shared between the two species. We show that six members of the proteasome degradation system are similarly expressed across MSCs derived from bone marrow, adipose tissue, amnion, and umbilical cord. Additionally, with the help of predictive models, we found that the expression profile of these genes correctly validated the identity of the MSCs across all the tissue sources tested. Moreover, using genetic interaction networks, we showed a possible link between these genes and antioxidant enzymes in the MSC antioxidant defense system, thereby pointing to their potential role in prolonging the life span of MSCs. According to our findings, members of the proteasome degradation system may serve as stemness-related markers.